Social inequalities: theoretical focus - Schwinn, Thomas (Soziologie - sociology in the German-Speaking World, 2021)
Das Kapitel Social Inequalities - Theoretical Focus erschien in Soziologie - Sociology in the German-Speaking World auf Seite 381.
Gesehen am 13.04.2021